2017
DOI: 10.1051/epjconf/201714003055
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation processes in Aeolian transport

Abstract: We investigate experimentally the relaxation process toward the equilibrium regime of saltation transport in the context of spatial inhomogeneous conditions. The relaxation length associated to this process is an important length in aeolian transport. This length stands for the distance needed for the particle flux to adapt to a change in flow conditions or in the boundary conditions at the bed. Predicting the value of this length under given conditions of transport remains an open and important issue. We cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…They observed the fetch effect in their study site with well‐sorted fine sand of 0.17 mm, but also observed a decay trend in transport rate after the critical fetch distance due to a negative feedback mechanism between saltation and wind, and non‐ideal surface conditions. Bauer, Sherman, & Wolcott (1992), Andreotti, Claudin, & Pouliquen (2010) and Selmani et al (2017) similarly observed a decay trend in their wind tunnel measurements, which exhibited an overshoot effect. Although observed in wind tunnels, this overshoot effect has not been observed in the field (i.e., agricultural fields or beaches) (Delgado‐Fernandez, 2010).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…They observed the fetch effect in their study site with well‐sorted fine sand of 0.17 mm, but also observed a decay trend in transport rate after the critical fetch distance due to a negative feedback mechanism between saltation and wind, and non‐ideal surface conditions. Bauer, Sherman, & Wolcott (1992), Andreotti, Claudin, & Pouliquen (2010) and Selmani et al (2017) similarly observed a decay trend in their wind tunnel measurements, which exhibited an overshoot effect. Although observed in wind tunnels, this overshoot effect has not been observed in the field (i.e., agricultural fields or beaches) (Delgado‐Fernandez, 2010).…”
Section: Introductionmentioning
confidence: 87%
“…Many researchers have studied the fetch effect and the corresponding critical fetch distance scale in wind tunnel environments (e.g., Andreotti, Claudin, & Pouliquen, 2010; Bagnold, 1941; Chen, Xiao, & Dong, 2020; Dong et al, 2004; Selmani et al, 2017) and during field experiments on coastal beaches and in deserts (e.g., Bauer et al, 2009; Bauer & Davidson‐Arnott, 2003; Davidson‐Arnott et al, 2005; Davidson‐Arnott et al, 2008; De Vries et al, 2014; Jackson & Cooper, 1999; Lynch, Jackson, & Cooper, 2016; van der Wal, 1998; Zhang et al, 2022; Zhang, Dong, & Zhao, 2012). The results of critical fetch distance and growth rate with distance downwind vary greatly as many of these studies are conducted during different experimental environments and that highlights a knowledge gap in the current literature (Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%